An integrated health sector response to violence against women in Malaysia: lessons for supporting scale up - Colombini Manuela; Mayhew Susannah H; Ali Siti; Shuib Rashidah; Watts Charlotte (BMC, 2012)
Abstract Background Malaysia has been at the forefront of the development and scale up of One-Stop Crisis Centres (OSCC) - an integrated health sector model that provides comprehensive care to women and children experiencing physical, emotional and sexual abuse. This study explored the strengths and challenges faced during the scaling up of the OSCC model to two States in Malaysia in order to identify lessons for supporting successful scale-up. Methods In-depth interviews were conducted with health care providers, policy makers and key informants in 7 hospital facilities. This was complemented by a document analysis of hospital records and protocols. Data were coded and analysed using NVivo 7. Results The implementation of the OSCC model differed between hospital settings, with practise being influenced by organisational systems and constraints. Health providers generally tried to offer care to abused women, but they are not fully supported within their facility due to lack of training, time constraints, limited allocated budget, or lack of referral system to external support services. Non-specialised hospitals in both States struggled with a scarcity of specialised staff and limited referral options for abused women. Despite these challenges, even in more resource-constrained settings staff who took the initiative found it was possible to adapt to provide some level of OSCC services, such as referring women to local NGOs or community support groups, or training nurses to offer basic counselling. Conclusions The national implementation of OSCC provides a potentially important source of support for women experiencing violence. Our findings confirm that pilot interventions for health sector responses to gender based violence can be scaled up only when there is a sound health infrastructure in place - in other words a supportive health system. Furthermore, the successful replication of the OSCC model in other similar settings requires that the model - and the system supporting it - needs to be flexible enough to allow adaptation of the service model to different types of facilities and levels of care, and to available resources and thus better support providers committed to delivering care to abused women.